Concepts in occupational therapy in relation to the ICF. - Haglund L; Henriksson C (Occupational Therapy International, 2003)
Occupational therapists need an acceptable terminology to describe a client's clinical performance. The language or terminology must be in harmony with common language in the health care system but also reflect occupational therapists' professional responsibility. The aim of this paper is to help clarify similarities and differences between concepts in occupational therapy and the International Classification of Functioning, Disability and Health (ICF). Two studies were completed in which items in the International Classification of Impairments, Disabilities and Handicaps (ICIDH-2) were compared with concepts from the Swedish version of the assessment of Motor and Process Skills (AMPS) and the Assessment of Communication and Interaction Skills (ACIS-S). An expert panel of occupational therapists served as raters and 33 clients with learning disabilities and mental health problems were assessed. The result showed that 12 (60%) of the skills items from the ACIS-S were found to be equivalent to items in then ICIDH-2. In total, 41% (n = 23) of the items in the AMPS or ACIS-S have a correlation higher then 0.60 with the ICIDH-2. The classification can serve as a useful tool for occupational therapists and supports communication between professions, but is not sufficient as a professional language for occupational therapists. Further research is indicated to examine how the ICF can be applied in occupational therapy and its implications on clinical practice.